The Direct and Indirect Relationships Within the Extended Trans-contextual Model for Moderate-to-vigorous Physical Activity - Mieziene, Brigita; Emeljanovas, Arunas; Putriute, Vitalija; Novak, Dario (Frontiers in Pediatrics, 2021)
Given the low levels of physical activity (PA) in adolescence, there are challenges to increasing students’ PA outside of the school setting. Thus, researchers emphasize the supportive role that physical education (PE) teachers can play in PA motivation both in and out of school (Dudley et al., 2012). The aim of the present study was to examine an expanded trans-contextual model (TCM) model for the transit of teachers’ perceived support of students’ autonomy in terms of contextual and situational motivation in PE to objectively measured moderate-to-vigorous physical activity (MVPA) in PE across different PE contents as well as to the motivational sequence for, and participation in, subjective MVPA during leisure time. This cross-sectional study involved 283 high school students, of whom 43.9 % were boys. The autonomous support students received and other motivational factors and objective measures of MVPA in PE and subjective MVPA in leisure time were measured. The results indicate that support for autonomy was significantly and directly related to needs satisfaction (β = 0.61, p < 0.001) and indirectly to autonomous motivation in PE (β = 0.19, p < 0.001) and leisure time (β = 0.16, p < 0.001), intention in PE (β = 0.03, p < 0.05) and leisure time (β = 0.07, p < 0.001), and leisure time MVPA (β = 0.04, p < 0.001), although not MVPA in PE. Gender was a significant covariate for both MVPA in PE (β = -0.62, p < 0.001) and MVPA in leisure time (β = -0.37, p < 0.001), with higher MVPA in boys than girls. This study filled a gap in the scientific literature by demonstrating the full motivational sequence resulting in actual MVPA in PE classes. It also demonstrated that the main goal of PE of enhancing PA not only in school but also outside of school is working. The main motivator is needs satisfaction based on PE teachers’ support.